2016
DOI: 10.1007/s13224-016-0907-x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic, Reproductive and Clinical Profile of Women Diagnosed with Advanced Cervical Cancer in a Tertiary Care Institute of Delhi

Abstract: Introduction Cervical cancer is one of the leading cancers among Indian women with estimated 123,000 new cases and 67,477 deaths in 2012. Cervical cancer is a multietiological disease. Factors such as low socioeconomic status, tobacco use, sexual and reproductive factors, HIV and other sexually transmitted diseases and long-term oral contraceptive use have been suggested as determinants. Assessment of socio-demographic profile and reproductive history gives a better picture of the determinants of cervical carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
1
15
1
4
Order By: Relevance
“…[4,5] In addition, various risk factors including socioeconomic status and sexual and reproductive factors may also be associated with cervical cancer which may vary in different geographical regions. [6] The present study was therefore conducted to assess the immunoexpression of p16 INK4a in premalignant and malignant lesions of the cervix and to correlate it with HPV 16 expression. In addition, it was also intended to study the various risk factors which may be associated with cervical cancer in this North Himalayan Region of India.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] In addition, various risk factors including socioeconomic status and sexual and reproductive factors may also be associated with cervical cancer which may vary in different geographical regions. [6] The present study was therefore conducted to assess the immunoexpression of p16 INK4a in premalignant and malignant lesions of the cervix and to correlate it with HPV 16 expression. In addition, it was also intended to study the various risk factors which may be associated with cervical cancer in this North Himalayan Region of India.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the most at the first age sexual intercourse for ≤ 18 years is 52.9%, this study was by the results of a study by Wulandari that obtained 59.2% [12]. Likewise, with the study conducted by Dahiya in India, the results were obtained 70.15% for first age sexual intercourse ≤ 18 years [5]. This is because biologically from the cervix is immature during adolescence, making it more susceptible to HPV infection, and other sexually transmitted diseases [13].…”
Section: Discussionmentioning
confidence: 64%
“…For the marital status is most married was 76.5%, by a study conducted by Dahiya et al in India, that the most cervical cancer was obtained at the marital status of 73.13% 5. The most employment status is 58.8%., the study conducted by Endarti et al, found that the highest employed status was work is 71% [10].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Human Papilloma Virus (HPV) is the most important etiologic factor in majority of cases of cervical cancer, with HPV DNA identified in approximately 95% of malignant cervical lesions. Other risk factors such as low socio-economic status, tobacco smoking, sexual habits, HIV, other sexually transmitted diseases, long-term oral contraceptive use, certain micronutrient deficiencies and genetic susceptibility have been suggested as determinants [3]. Treatment depends on the clinical stage of the disease according to the classification of the International Federation of Gynecology and Obstetrics (FIGO) [4,5].…”
Section: Introductionmentioning
confidence: 99%